Seasonal richness and community structure of the epigeal ants in forest fragments of the Colombian Orinoquian flooded savanna - Agudelo-Martínez, Juan Carlos; Pérez-Buitrago, Néstor (Revista de Biología Tropical, 2020)
Introduction: Ants are one of the most abundant and diverse taxonomic groups. Their ecological fidelity allows them to carry out indispensable roles for the adequate functioning of terrestrial ecosystems. Objective: Evaluate seasonal biodiversity dynamics (richness and abundance) of ant species associated with fragments of forest and the surrounding floodplain savanna at the municipality of Arauca, Colombia. Methods: Ants were collected using three complementary techniques (pitfall, Winkler sac and direct collect), in eight forest fragments where linear transects with seven sampling points were installed. Non-parametric estimators and the complementarity index were used to describe the ant community structure. The climatic seasons (dry and rainy) and environments (floodplain, edge, and forest) were compared using species richness and abundance. The relationship of ant species by each sampling points was evaluated with a non-metric multidimensional scaling analysis (NMDS) and the forest fragment attributes were related to species richness through a canonical correspondence analysis (CCA). Results: We found 30 496 specimens corresponding to 104 species, 37 genera, and eight subfamilies. The best-represented genera were: Pheidole, Camponotus, Solenopsis, and Dolichoderus. The richness nonparametric estimators showed that the ant community oscillates between 107 and 119 species, no differences were detected in species richness and abundance in terms of the climatic seasons (dry and rainy). There were differences in species richness between floodplain with both edge and forest environments. Ant richness fragments of the forest was related by fragment variables such as area, perimeter, fractal dimension, and compactness index. Conclusions: No differences in species richness and abundance were detected between the dry and rainy seasons, which suggests that the species are permanent residents of the study area. There must be mechanisms that allow these ant species to cope with the rainy season. There was a direct relationship between different forest fragment characteristics and ant species richness. This work expands the knowledge of the ant species present in the north of the Colombian Orinoquia.